La vía romana de Berducedo a Bustantigo en el Concejo de Allande (Asturias) - Santos Yanguas, Narciso (Gerión. Revista de Historia Antigua, 2002)
The road system of the first centuries of our age explains in itself, and within the South-Western area of Asturias, the process of assimilation of Roman organization. The development of settlements (castra) and exploitation of golden deposits will be carried our along this road, belonging the towns of Berducedo and Bustantigo in the Concejo of Allande. The economic basics (mining exploitations) becomes the main clue to understand the process of romanization of this Asturian region.